No moderating influence of education on the association between changes in hippocampus volume and memory performance in aging - Lövdén, M; Pagin, A; Bartrés-Faz, D; Boraxbekk, C-J; Brandmaier, AM; Demnitz, N; Drevon, CA; Ebmeier, KP; Fjell, AM; Ghisletta, P; Gorbach, T; Lindenberger, U; et al. (Elsevier, 2023)
Contemporary accounts of factors that may modify the risk for age-related neurocognitive disorders highlight education and its contribution to a cognitive reserve. By this view, individuals with higher educational attainment should show weaker associations between changes in brain and cognition than individuals with lower educational attainment. We tested this prediction in longitudinal data on hippocampus volume and episodic memory from 708 middle-aged and older individuals using local structural equation modeling. This technique does not require categorization of years of education and does not constrain the shape of relationships, thereby maximizing the chances of revealing an effect of education on the hippocampus-memory association. The results showed that the data were plausible under the assumption that there was no influence of education on the association between change in episodic memory and change in hippocampus volume. Restricting the sample to individuals with elevated genetic risk for dementia (APOE ε4 carriers) did not change these results. We conclude that the influence of education on changes in episodic memory and hippocampus volume is inconsistent with predictions by the cognitive reserve theory.